2008
DOI: 10.1111/j.1447-0349.2008.00568.x
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of home visits by mental health nurses for Japanese women with post‐partum depression

Abstract: Post-partum depression affects 10-13% of Japanese women, but many do not receive appropriate treatment or support. This intervention study evaluated the effectiveness of home visits by mental health nurses for Japanese women with post-partum depression. Eighteen post-partum women met the inclusion criteria and were randomly allocated into the intervention (n = 9) or control (n = 9) group at 1-2 months after giving birth. The intervention group received four weekly home visits by a mental health nurse. Control … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
25
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(28 citation statements)
references
References 35 publications
3
25
0
Order By: Relevance
“…One study reported that the women had learned a “psychological language,” and many studies referred to an improvement in the understanding and perception of PPD. Women also reported that their confidence in parenting had increased as a result of information they received in this respect during their intervention . Many women reported improvements in their relationships both with their infant and significant others .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…One study reported that the women had learned a “psychological language,” and many studies referred to an improvement in the understanding and perception of PPD. Women also reported that their confidence in parenting had increased as a result of information they received in this respect during their intervention . Many women reported improvements in their relationships both with their infant and significant others .…”
Section: Resultsmentioning
confidence: 99%
“…Based on the criteria set by Walsh and Downe, the majority of studies included were of very good methodologic quality, with only one exception . Finally, only 2 of the 17 included studies referred to reflexivity, a key component of quality control in qualitative research …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Two examples of nursing care could be applicable to primary health care in Brazil: (1) a qualitative study of Japanese women's perceptions about nurses' home visits indicated women believed their PPD improved because they had opportunities to clarify their thoughts with nurses and disperse negative feelings (Tamaki ); and (2) a study that investigated American women's perceptions about screening and counselling during PPD found nurses can play a fundamental role in identifying perinatal depression; the women were receptive to being screened and counselled by them (Segre et al . ).…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have shown that home visits by nurses can contribute to positive mental health, social changes and an increase in the women's quality of life in postpartum (Beeber et al . , Tamaki ).…”
Section: Discussionmentioning
confidence: 97%